2015
DOI: 10.1016/j.chroma.2014.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Application of ion exchange and extraction chromatography to the separation of actinium from proton-irradiated thorium metal for analytical purposes

Abstract: Actinium-225 (t1/2=9.92d) is an α-emitting radionuclide with nuclear properties well-suited for use in targeted alpha therapy (TAT), a powerful treatment method for malignant tumors. Actinium-225 can also be utilized as a generator for (213)Bi (t1/2 45.6 min), which is another valuable candidate for TAT. Actinium-225 can be produced via proton irradiation of thorium metal; however, long-lived (227)Ac (t1/2=21.8a, 99% β(-), 1% α) is co-produced during this process and will impact the quality of the final produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 20 publications
3
53
0
Order By: Relevance
“…Additionally, there had to be a method to remove the Lu III from Ac III after the experiment, so that the precious actinium sample could be recycled for future studies. Consistent with many actinium/lanthanide separation studies, 17,5,24,25,3238 we observed that liquid/liquid extraction chromatography (branched DGA; Eichrom) was effective for purifying Ac III from Lu III . As an example, “proof-of-principle” experiments using stable Lu III (0.5 mg) spiked with a radioactive 173 Lu tracer [ t 1/2 = 1.37(1) y; 5.8 kBq; 3.6 × 10 11 atoms] 3 and short-lived 225 Ac [ t 1/2 = 10.0(1) d; 8.8 kBq; 1.1 × 10 10 atoms] demonstrated feasibility.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, there had to be a method to remove the Lu III from Ac III after the experiment, so that the precious actinium sample could be recycled for future studies. Consistent with many actinium/lanthanide separation studies, 17,5,24,25,3238 we observed that liquid/liquid extraction chromatography (branched DGA; Eichrom) was effective for purifying Ac III from Lu III . As an example, “proof-of-principle” experiments using stable Lu III (0.5 mg) spiked with a radioactive 173 Lu tracer [ t 1/2 = 1.37(1) y; 5.8 kBq; 3.6 × 10 11 atoms] 3 and short-lived 225 Ac [ t 1/2 = 10.0(1) d; 8.8 kBq; 1.1 × 10 10 atoms] demonstrated feasibility.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, this procedure was successfully applied in recovering 227 Ac after the XAFS experiment. Although similar elution profiles were previously reported using trace quantities of actinium and lanthanides, 4,17,18,36,3844 our separation demonstrated that the DGA process accommodated a large mass range. This spanned picogram (pg) to microgram (μg) quantities with successful separations both at the tracer level ( 225 Ac = 1.1 × 10 10 atoms; 173 Lu = 3.6 × 10 11 atoms) and using large masses ( 227 Ac = 7.4 × 10 4 kBq, 7.4 × 10 16 atoms, 2.8 × 10 –5 g; stable Lu = 1.7 × 10 18 atoms, 5.0 × 10 –4 g).…”
Section: Resultssupporting
confidence: 86%
“…In one study of the separation of actinium(II) from thorium(IV) and radium(II), thorium(IV) was eluted with citric acid from AG50W-X8 resin. The procedure did however include several other steps with the use of strong acids and extraction chromatography resin DGA (Eichrom) [266]. Cation exchange resins DOWEX 50W-X8, AG50W-X8 and Merk I have in another study been used for the sorption of calcium (II), barium(II) and radium(II) with desorption by the aid of tartrate, EDTA and citrate, but the pH (>8) was high for desorption of radium(II) and no separation of thorium(II) from radium(II) was studied [267].…”
Section: Selected Methods For Column Separation and Purification Of Tmentioning
confidence: 99%
“…More recently, research efforts have been undertaken by the US Department of Energy to achieve cyclotron-production of 225 Ac using high-energy proton irradiation of natural thorium targets (Radchenko et al, 2015a; Radchenko et al, 2015b; Weidner et al, 2012). However, 227 Ac contamination is a side-product of this irradiation (approximately ≈0.3%).…”
Section: Introductionmentioning
confidence: 99%